2019
DOI: 10.1007/s10120-019-00979-z
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted gastrectomy for gastric cancer: a European perspective

Abstract: Gastrectomy is the mainstay treatment for gastric cancer. To reduce the associated patient burden, minimally invasive gastrectomy was introduced in almost 30 years ago. The increase in the availability of surgical robotic systems led to the first robotic-assisted gastrectomy to be performed in 2002 in Japan. Robotic gastrectomy however, particularly in Europe, has not yet gained significant traction. Most reports to date are from Asia, predominantly containing observational studies. These cohorts are commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 90 publications
(77 reference statements)
1
49
0
Order By: Relevance
“…Currently, reports in the field of robotic-assisted gastrectomy are increasing year by year, and most of them are observational studies with patients who presented at a relatively early stage of disease 20,21 . These studies commonly enroll patients with different TNM stages and who have underwent different types of stomach resection, and as such, there are many factors that may affect the authenticity of their results 22 . Another concern is that approximately half of the world's gastric cancer cases occur in China, most of which are in an advanced stage (T2-4aN0-3M0) at the time of initial diagnosis, and China plays a major role in the global burden of gastric cancer 3,23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, reports in the field of robotic-assisted gastrectomy are increasing year by year, and most of them are observational studies with patients who presented at a relatively early stage of disease 20,21 . These studies commonly enroll patients with different TNM stages and who have underwent different types of stomach resection, and as such, there are many factors that may affect the authenticity of their results 22 . Another concern is that approximately half of the world's gastric cancer cases occur in China, most of which are in an advanced stage (T2-4aN0-3M0) at the time of initial diagnosis, and China plays a major role in the global burden of gastric cancer 3,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, subsequent subgroup analyses of surgical complications revealed that the rate of pancreatic fistula was significantly lower in the RADG group than in the LADG group (0.4% vs. 2.8%, P = 0.044), which is consistent with previous studies 37,38 . The underlying cause for this difference may be the advantage that the robot has in its precision and stability, and it is not likely that the robot will damage the pancreas when cleaning lymph nodes and clearing the pancreatic capsule 22 . Ojima et al indicated that amylase activity from abdominal drainage fluid were higher in the laparoscopic gastrectomy group than in the robotic group on postoperative day 1 (P = 0.028) 39 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the two-dimensional visualization and limited movement of laparoscopic instruments make it difficult to perform lymphadenectomy precisely. Robotic surgical system overcomes those limitations including eliminating the traces of physiologic human tremor and increasing dexterity through its typical internal articulated endoscopic wrist (EndoWrist™ System) for a precise lymphadenectomy with a 3D high-resolution images at the console [ 15 ]. In 2002, Hashizume reported robotic-assisted gastrectomy for the first time [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, robotic surgery has been demonstrated to obtain similar or even better anatomical and operative conditions compared to the traditional laparoscopic approach during gastric resection [ 15 , 17 21 ]. However, most of the reported cases were early gastric cancer (EGC) [ 22 , 23 ], and few studies have retrospectively compared robotic-assisted total gastrectomy (RATG) with LATG for advanced gastric cancer (AGC) [ 15 , 24 ]. The aim of this study is to evaluate the feasibility and safety of RATG and LATG for AGC using the propensity score matching (PSM) method.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Novel strategies for advanced GC patients are emerging, including metabolism-targeted cancer therapy, which showed extensive application value. [31][32][33][34][35][36] High level of glycolysis and glucose uptake is a significant hallmark in cancer and GLUT1 is the main rate limiting step of glucose uptake. 37,38 Existing studies have proven that elevated GLUT1 expression is observed in most solid cancers.…”
Section: Discussionmentioning
confidence: 99%